2019
DOI: 10.1177/0271678x19875201
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of histone deacetylase 3 by MiR-494 alleviates neuronal loss and improves neurological recovery in experimental stroke

Abstract: HDAC3 is an essential negative regulator of neuronal plasticity and memory formation. Although a chemical inhibitor has been invented, little is known about its endogenous modulators. We explored whether miR-494 affects HDAC3-mediated neuronal injury following acute ischemic stroke. A substantial increase in plasma miR-494 was detected in AIS patients and was positively associated with the mRS at one year after symptom onset. The miR-494 levels were transiently increased in the infarcted brain tissue of mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
24
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 33 publications
3
24
0
Order By: Relevance
“…Importantly, in the case of the latter miRNA, protection against the development of the tumors comes at a cost of elevated susceptibility to neurotoxicity, after exposure to ischemia/ reperfusion for example. Notably, knockdown of hsa-miR-494-5p reverses the neurotoxic phenotype in multiple models (Song et al, 2017;Deng et al, 2019;Zhao et al, 2019a;Zhao et al, 2019b). Hsa-miR-494-5p-dependent antagonistic relationships between gliomagenesis and neurotoxicity are intriguing, as they support previously noted decrease in odds of the development of brain tumors in patients with schizophrenia (Grinshpoon et al, 2005;Levav et al, 2007;.…”
Section: Discussionsupporting
confidence: 57%
“…Importantly, in the case of the latter miRNA, protection against the development of the tumors comes at a cost of elevated susceptibility to neurotoxicity, after exposure to ischemia/ reperfusion for example. Notably, knockdown of hsa-miR-494-5p reverses the neurotoxic phenotype in multiple models (Song et al, 2017;Deng et al, 2019;Zhao et al, 2019a;Zhao et al, 2019b). Hsa-miR-494-5p-dependent antagonistic relationships between gliomagenesis and neurotoxicity are intriguing, as they support previously noted decrease in odds of the development of brain tumors in patients with schizophrenia (Grinshpoon et al, 2005;Levav et al, 2007;.…”
Section: Discussionsupporting
confidence: 57%
“…HDAC3 inhibition exerted protective effects against diabetic stroke via the enhancement of oxidative stress, inhibition of apoptosis, and improvement of autophagy, all of which might be mediated by the upregulation of Bmal1 [50]. Furthermore, miR-494 in MCAO mouse model produced neuroprotective effects by reducing the expression levels of HDAC3 in neurons [51].…”
Section: Discussionmentioning
confidence: 97%
“…HDAC3 inhibitors acted on several cell types in the CNS, including neurons, astrocytes, and microglia [52]. miR-193b-3p and its target HDAC3 may also be regulated by other mechanisms, including autophagy or apoptosis [49,51], possibly leading to neuroprotective effects. Further studies are required to account for the beneficial mechanisms of miR-193b-3p in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…As discussed above, multiple MMPs could be regulated by the HDAC family, including HDAC1, HDAC2, HDAC3, and HDAC7. Our previous study suggested that HDAC3 was a direct target of miR-494 [34]. It is possible that miR-494 could regulate these MMPs by targeting HDAC3 or other members of the HDAC family.…”
Section: Discussionmentioning
confidence: 99%